Comments on Reply to Letter to the Editor-in-Chief by T. Erdik [1] - Varol, Yasin; Avci, Engin; Koca, Ahmet; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2009)
[Abstract Not Available]
Keywords: Fuzzy Inference System; Natural-Convection; Anfis; Performance; Prediction; Enclosure